Respuesta :
Answer:
[tex]\displaystyle f(x)=\left(x+\frac{1}{2}\right)^2+\frac{3}{4}[/tex]
Step-by-step explanation:
We are given the function:
[tex]f(x)=x^2+x+1[/tex].
And we want to turn this into vertex form.
Note that our given function is in the standard form:
[tex]f(x)=ax^2+bx+c[/tex]
In other words, a = 1, b = 1, and c = 1.
To convert from standard form to vertex form, we can either: (1) complete the square, or (2) find the vertex manually.
In most cases, the second method is more time efficient.
Vertex form is given by:
[tex]f(x)=a(x-h)^2+k[/tex]
Where a is the leading coefficient and (h, k) is the vertex.
We have already determined that a = 1.
Find the vertex. The x-coordinate of the vertex of a quadratic is given by:
[tex]\displaystyle x=-\frac{b}{2a}[/tex]
Therefore, our point is:
[tex]\displaystyle x=-\frac{(1)}{2(1)}=-\frac{1}{2}[/tex]
To find the y-coordinate or k, substitute this value back into the function:
[tex]\displaystyle f\left(-\frac{1}{2}\right)=\left(-\frac{1}{2}\right)^2+\left(-\frac{1}{2}\right)+1=\frac{3}{4}[/tex]
Thus, the vertex is (-1/2, 3/4). So, h = -1/2 and k = 3/4.
Hence, the vertex form is:
[tex]\displaystyle f(x)=(1)\left(x-\left(-\frac{1}{2}\right)\right)^2+\left(\frac{3}{4}\right)[/tex]
Simplify:
[tex]\displaystyle f(x)=\left(x+\frac{1}{2}\right)^2+\frac{3}{4}[/tex]